Perancangan buku Visual Cara Membatik Pada Batik Tegalan Dalam Upaya Pelestarian Budaya Indonesia - Puri Sulistiyawati; Dimas Irawan Ihya Ulumuddin; Dwi Puji Prabowo; Alif Aji Yasin; Dzuha Hening Yanuarsari (UNIVERSITAS STEKOM, 2024)
Tegalan Batik is a cultural heritage that faces challenges in its preservation, especially related to the lack of interest of the younger generation in learning batik. This research aims to analyze the obstacles faced in the development of Tegalan batik and evaluate the effectiveness of illustrated books as an educational medium to increase the younger generation's interest and understanding of Tegalan batik. Using descriptive qualitative methods, data was collected through interviews, observation and literature review. The research results show that the lack of regeneration and lack of markets are the main factors in the decline in the younger generation's interest in batik. Illustrated books can be an effective solution in Tegalan batik education